Pengembangan Web Pembelajaran Biologi Berbasis Socio-Scientific Issues (SSI) Topik Sistem Pencernaan untuk Mengembangkan Literasi Kesehatan Siswa SMA - Icha Galuh Puspita (Jurnal Pendidikan Biologi Undiksha, 2022)
The aims of this study to determine  feasibility of developing a biology learning web based on Socio-Scientific Issues (SSI) in digestive system to develop student’s health literacy. This is a Research and Development (R&D) with ADDIE model. Data was collected using an assessment instrument with a Likert scale and a Guttman scale which were analyzed descriptively qualitatively and quantitatively. The results of this study indicate that the web sufficient the criteria based on the results of assessment and suitable for use as teaching materials in learning.